(untitled) - Shelly, Gary B.; Gary B. Shelly; Thomas J. Cashman; Dolores J. Wells (Australia,United Kingdom, 2003)
Using the Shelly Cashman Series step-by-step, screen-by-screen proven approach to learning, students of all levels will stay on track while learning the latest Dreamweaver MX skills. Starting from scratch, each user will build a fully functional web site in the Dreamweaver MX environment that they can easily incorporate into their Web portfolio. Dreamweaver MX is the latest in building Web sites and Internet applications, and using texts from the Shelly Cashman Series is your solution to teaching it!
Keywords: Dreamweaver (Computer file)